Study of the efficiency and safety of Ladasten therapy in patients with cardiovascular disease - F. Yu Kopylov; Yu. M Nikitina; E. A Makukh; A. L Syrkin (КардиоСоматика, 2010)
A trial was carried out to study the efficiency and safety of therapy with the new antiasthenic drug Ladasten. The findings suggest its high safety and efficiency and good tolerability of Ladasten in the treatment of asthenia and asthenic spectrum disorders, the development of which is associated with cardiovascular disease.